AGENT-BASED COLLABORATIVE PLATFORM FOR COORDINATING CONCURRENT NEGOTIATION ACTIVITIES - Adina-Georgeta CREȚAN (Challenges of the Knowledge Society, 2021)
Maintaining the sustainability of an organization on the market and their performance in a competitive market is very difficult to achieve. In this dynamic environment, organizations decide to cooperate, becoming partners in a virtual enterprise. In order to work efficiently, the partners must collaborate and coordinate their negotiation activities. This paper proposes an agent-based collaborative platform for coordinating concurrent negotiations among organizations acting in the same industrial market. The underlying complexity is to model the dynamic environment where multi-attribute and multi-participant negotiations are racing over a set of heterogeneous resources.